A judge’s integrity as a deontological norm of his/her behavior - Valentyna, Kravchuk (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article is devoted to the study of integrity as a deontological norm of the behavior of judges, the obligation of this requirement for judges is substantiated, the meaningful characteristics of virtuous behavior and indicators of dishonest behavior of judges are analyzed. Integrity is revealed in a combination of two aspects - external (visible, and therefore can be monitored by the public and controlling bodies, as it is manifested in the lifestyle, behavior and actions of a person) and internal, which involves the moral and mental wholeness, honesty of a person, which determine her behavior, her decisions and actions. Judges are obliged to demonstrate and promote high standards of behavior, so the integrity of a judge can be considered as the result of strict adherence to ethical standards and principles in the behavior of each judge, and therefore integrity is a deontological norm of behavior and is a mandatory requirement for professional (as well as non-professional) activity judges The integrity of judges contributes to the formation of trust and respect for the judiciary in general, especially given the fact that nowadays the demand for justice is a priority. Therefore, judges must make every effort to ensure that their behavior is impeccable and undoubtedly appears so from the position of an outside observer. Content indicators (indicators) of integrity/dishonesty of judges should be clearly defined, and the mechanism for checking the integrity of a judge (candidate for the post of judge) should be transparent and clear. The developers of the Indicators used by the Public Integrity Council have so far failed to achieve this completely.